2021
DOI: 10.1021/acs.langmuir.1c00961
|View full text |Cite
|
Sign up to set email alerts
|

Droplet Nucleation and Growth in the Presence of Noncondensable Gas: A Molecular Dynamics Study

Abstract: The presence of noncondensable gas (NCG) followed by undesirable heat transfer deterioration cannot be avoided in some situations. In this work, droplet nucleation and growth for the Ar−Ne mixed system are investigated using molecular dynamics simulation. Different droplet state transition modes corresponding to the subcooling degree or NCG content are obtained. The interaction between NCG and a droplet caused by gas enrichment near the solid surface is considered to explain the droplet wetting state during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…As shown in Figure 6a, the number of liquid molecules first oscillates around N liq = 10 and then increases rapidly at τ = 1000 ps on the partially wetting surface while showing an instant increase once the vapor temperature drops to 400 K (τ = 0 ps) on the completely wetting surface. This distinctive condensation process on the partially wetting surface has also been observed in previous studies, 45 indicating the significant differences between the heterogeneous condensation on partially and completely wetting surfaces.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure 6a, the number of liquid molecules first oscillates around N liq = 10 and then increases rapidly at τ = 1000 ps on the partially wetting surface while showing an instant increase once the vapor temperature drops to 400 K (τ = 0 ps) on the completely wetting surface. This distinctive condensation process on the partially wetting surface has also been observed in previous studies, 45 indicating the significant differences between the heterogeneous condensation on partially and completely wetting surfaces.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The condensation simulations are performed using the GCMC+MD method, which has been demonstrated to be effective in simulating condensation processes. The GCMC method is adopted to maintain the vapor pressure of the system through the whole simulation by inserting or deleting fluid molecules in a specific region. The velocity-Verlet algorithm is utilized to update the particle velocities and positions.…”
Section: Methodsmentioning
confidence: 99%
“…[ 43 ] Although the nucleation densities shown in Figure 3 are low compared to the typical values reported on metallic substrates, [ 52,53 ] we emphasize here that, in addition to the rigidity of the substrate, the nucleation density during condensation is also sensitive to other factors such as surface roughness, level of subcooling [ 54 ] and fraction of non‐condensable gases in water vapor. [ 55 ] Additionally the thermal conductivity of these soft organogels of around 0.2 W mK −1[ 56,57 ] is much lower compared to metals, such as Copper and Aluminium, that are typically used in heat transfer applications. Thus we have compared the dewing performance of P10L0 and hydrophobic copper substrates under same atmospheric humidity and subcooling conditions.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, researchers have begun to seek inspiration from the natural world to pursue better water vapor condensation performance. The condensation processes on various bionic surfaces with special wettabilities and micro/nanostructures have attracted tremendous attention. Based on the special surface functions and characteristics on creature surfaces, such as the self-cleaning function on the locus, the antifog characteristics on dragonfly wings, and the directional detachment of condensed droplets on the butterfly surface, diverse bionic surfaces were designed, and the efficient vapor condensation process was put forward, which included the following condensation characteristics: rapid droplet nucleation, high growth rate, and effective removal of condensed droplets. Typically, inspired by Namble dessert beetles, the simplified beetle bionic surface with hybrid wettabilities was constructed for water vapor condensation experiments, and researchers discovered that the condensation performance on beetle bionic surfaces with different hydrophilic micropillar diameters was better than that on the surface patterned only with hydrophobic nanograss . Moreover, through constructing nanopillars with hybrid wettabilities on the surface, it was observed that the condensation performance was improved compared with that on the surface with homogeneous hydrophobic nanopillars, and the enhancement of heat and mass transfer performance could be attributed to the steady dropwise condensation and regular nucleation .…”
Section: Introductionmentioning
confidence: 99%